2021
DOI: 10.3389/fcell.2021.691410
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Regulatory Mechanisms Involved in Liver Cancer Stem Cell Properties in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the predominant form of primary liver cancer and one of the leading causes of cancer-related deaths worldwide. A growing body of evidence supports the hypothesis that HCC is driven by a population of cells called liver cancer stem cells (LCSCs). LCSCs have been proposed to contribute to malignant HCC progression, including promoting tumor occurrence and growth, mediating tumor metastasis, and treatment resistance, but the regulatory mechanism of LCSCs in HCC remains unclear. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 152 publications
0
13
0
Order By: Relevance
“…The biological mechanism of hepatocarcinogenesis and its progression are complex. Accumulating evidence indicates the significance of liver cancer stem cells (LCSCs), which are small-population liver cancer cells with the potential for self-renewal and tumorigenicity, in tumorigenesis, recurrence, and metastasis [4,5]. Despite numerous studies having revealed the molecular basis for LCSCs, which includes genetic mutations, epigenetic disruption, signaling pathway dysregulation, and/or microenvironment remodeling [5], none of them have brought about an effective solution for eradicating LCSCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological mechanism of hepatocarcinogenesis and its progression are complex. Accumulating evidence indicates the significance of liver cancer stem cells (LCSCs), which are small-population liver cancer cells with the potential for self-renewal and tumorigenicity, in tumorigenesis, recurrence, and metastasis [4,5]. Despite numerous studies having revealed the molecular basis for LCSCs, which includes genetic mutations, epigenetic disruption, signaling pathway dysregulation, and/or microenvironment remodeling [5], none of them have brought about an effective solution for eradicating LCSCs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, glycolytic inhibitor 2-deoxy-D-glucose (2-DG) has drastically inhibited the tumorigenicity and sorafenib resistance of LCSCs [16]. However, the plasticity of its metabolic phenotype is the main obstacle in targeting LCSCs [4,5]. Therefore, the energy sources for LSCSs, other than the metabolic phenotypes, need to be better understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several stemness-associated signaling pathways, such as Wnt/尾-catenin signaling, Notch signaling, and JAK/STAT signaling, also greatly contribute to stemness properties in HCC [39]. In HCC, stemness properties are closely associated with drug resistance, tumor metastasis, and recurrence [39]. Stemness properties are closely associated with the EMT phenotype, which was previously reported to contribute to sorafenib resistance in HCC [40,41].…”
Section: Discussionmentioning
confidence: 96%
“…The maintenance of stemness properties relies on the activation of stemness-associated genes, such as Sox2, OCT4, and Nanog [38]. Moreover, several stemness-associated signaling pathways, such as Wnt/尾-catenin signaling, Notch signaling, and JAK/STAT signaling, also greatly contribute to stemness properties in HCC [39]. In HCC, stemness properties are closely associated with drug resistance, tumor metastasis, and recurrence [39].…”
Section: Discussionmentioning
confidence: 99%
“…The poor prognosis and response to therapy of HCC is in part due to the presence of cancer stem cells (CSCs), an immune-privileged cell population that can evade immune surveillance more effectively than non-CSCs (6,7). Liver cancer stem cells (LCSCs) are a subset of hepatocarcinoma cells with pluripotent and self-renew properties which are related to the major malignant phenotypes of HCC (8)(9)(10). The expression of CSC-related genes such as NANOG, SOX2 and OCT4 can be promoted by oncogenes and/or Original Article Inhibitory effects of LOXL2 knockdown on cellular functions of liver cancer stem cells overexpression of oncoproteins such as the HBV envelope protein PreS1, thereby driving the malignant biological behaviors of LCSCs (11).…”
Section: Introductionmentioning
confidence: 99%